"Operating spacecraft around comets: Evaluation of the near-nucleus environment". (June 2022) - Lisse, C.M.; Combi, M.R.; Farnham, T.L.; Russo, N. Dello; Sandford, S.; Cheng, A.F.; Fink, U.; Harris, W.M.; McMahon, J.; Scheeres, D.J.; Weaver, H.A.; Leary, J.
Abstract: We present a study of the current state of knowledge concerning spacecraft operations and potential hazards while operating near a comet nucleus. Starting from simple back of the envelope calculations comparing the cometary coma environment to benign conditions on Earth, we progress to sophisticated engineering models of spacecraft behavior, and then confront these models with recent spacecraft proximity operations experience (e.g., Rosetta ). Finally, we make recommendations from lessons learned for future spacecraft missions that enter into orbit around a comet for long-term operations. All of these considerations indicate that, with a proper spacecraft design and operations planning, the near-nucleus environment can be a relatively safe region in which to operate, even for an active short period comet near perihelion with gas production rates as high as 10 29 molecules/s. With gas densities similar to those found in good laboratory vacuums, dust densities similar to Class 100 cleanrooms, dust particle velocities of 10's of m/s, and microgravity forces that permit slow and deliberate operations, the conditions around a comet are generally more benign than a typical day on Mars. Even in strong dust jets near the nucleus' surface, dust densities tend to be only a few grains/cm 3, about the same as in a typical interior room on Earth. Stochastic forces on a modern spacecraft with tens of square meters of projected surface area can be accounted for using modern Attitude Control Systems to within tens of meters' navigation error; surface contamination issues are only important for spacecraft spending months to years within a few kilometers of the nucleus' surface; and the issues the Rosetta spacecraft faced, confusion of celestial star trackers by sunlit dust particles flying past the spacecraft, will be addressed using the next generation of star trackers implementing improved transient rejection algorithms. Highlights: The cometary near-nucleus environment is safe for remotely operated spacecraft to operate in. This environment is more benign than a day on Mars or a Class 100 clean room. The highly successful Rosetta mission experienced minimal side effects due to operations in the near-nucleus comet environment. The minimal side effects can be ameliorated by flying instrument covers, avoiding active jet regions, and implementing modern star trackers with advanced false positive rejection algorithms.